2022
DOI: 10.1155/2022/7854297
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance and Potential Mechanism of Prolyl 3-Hydroxylase 1 in Hepatocellular Carcinoma

Abstract: Background. Prolyl 3-hydroxylase 1 (P3H1) is essential for human collagen synthesis. Here, we investigated its relevance to multiple cancers, especially hepatocellular carcinoma (LIHC). Methods. We estimated the relationship of P3H1 with 33 cancers using publicly available databases. And immunohistochemistry was utilized to verify the P3H1 expression in liver, gastric, colon, pancreatic, and rectal cancer. Then, we attenuated P3H1 expression in BEL-7402 and HLF cells by lentivirus technology and assessed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Previous literature has reported that PSMD14 can enhance the growth and metastasis of HCC by acting as a deubiquitinase to stabilize GRB2 23 . P3H1 was found to be upregulated in most tumors, and its knockdown significantly reduced the proliferation, migration, and invasion of HCC cells 24 . CENPA has also been reported to have predictive value in the development of HCC 25 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous literature has reported that PSMD14 can enhance the growth and metastasis of HCC by acting as a deubiquitinase to stabilize GRB2 23 . P3H1 was found to be upregulated in most tumors, and its knockdown significantly reduced the proliferation, migration, and invasion of HCC cells 24 . CENPA has also been reported to have predictive value in the development of HCC 25 .…”
Section: Discussionmentioning
confidence: 91%
“…23 P3H1 was found to be upregulated in most tumors, and its knockdown significantly reduced the proliferation, migration, and invasion of HCC cells. 24 CENPA has also been reported to have predictive value in the development of HCC. 25 G6PD has been shown to target cytochrome P450 reductase and inhibit ferroptosis in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…P3H1 expression levels may be used as an independent prognostic factor for patients with LIHC. Moreover, P3H1 knockdown greatly reduced the capacity of liver cancer cells to proliferate, migrate, and invade 40 .P3H1 expression levels may be used as a separate prognostic factor for patients with LIHC. Moreover, P3H1 knockdown greatly reduced the capacity of liver cancer cells to proliferate, migrate, and invade.…”
Section: Discussionmentioning
confidence: 99%
“…The lysates were then centrifuged at 12,000 rpm at 4 °C for minutes to remove debris, and the resulting supernatants were collected for electrophoresis. Western blotting was performed according to the protocol described in our previous study [ 26 ]. The primary antibodies used for the western blotting were TNF-α (Servicebio, China), IL-1β (Servicebio, China), and Tubulin-β (Abways Technology, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%